Analysis of the Accuracy of Clinical Diagnosis and PA Diagnosis in Appendectomy Patients at AN-NISA Tangerang Hospital Period 2019-2024 - Siti Maryam, Sarah; Nurusshofa, Zahra; Anisah, Anisah; El Anshory, Riza; Jantika, Dewi (Publikasi Indonesia, 2024)
Appendicitis is inflammation of the vermiform appendix caused by a blockage in the lumen of the appendix. Anatomic pathology examination is considered the gold standard in confirming the diagnosis of appendicitis, but this examination not always carried out. Method: in this study used descriptive cross-sectional with the aim of comparing the clinical diagnosis and Pathology Anatomy diagnosis of 80 cases of appendectomy at AN-NISA Tangerang Hospital during the period 2019-2024. This study also aims to look at the incidence of malignancy in appendectomy. The results of the 80 cases carried out showed that 7 cases were malignant, 8 cases of appendicitis tuberculosis, 4 cases of malignancy which were initially clinically diagnosed as non-malignant, and 4 cases of tuberculosis which were initially diagnosed as non-tuberculosis. This study found that age was associated with the incidence of malignancy in the appendix (P<0.05). This study also found that patients aged >40 years had a 1,233 times higher risk of experiencing malignancy in the appendix than patients aged <40 years. Conclusion: In a number of cases, clinically significant impacts were found if Pathology Anatomy examination was not carried out. This study recommends pathology anatomy examination during appendectomy, especially in the age group >40 years.